Preliminary observations on the patterns of co-occurrence of Black fly (Diptera: Simuliidae) larvae and some of their potential macroinvertebrate predators - Figueiró,Ronaldo (2020)
ABSTRACT Biotic factors such as predation, although important drivers of the black fly community, are rarely investigated in the literature. This study aimed to test the hypothesis that the patterns of co-occurrence of black fly larvae and its potential predators is not random and that there is a correlation between its frequencies and Simuliidae larvae abundances. Larvae were sampled from two localities in the Pedra Branca State Park, Rio de Janeiro, Brazil, during the dry season in june 2018. We collected Simulium pertinax Kollar, 1832, Simulium subpallidum Lutz, 1910, Simulium (Inaequalium) sp., Simulium (Psaroniocompsa) sp. and Simulium (Trichodagmia) sp. The predators families present were Perlidae, Hydropsychidae, Leptoceridae, Libellulidae and Chironomidae. The null models showed that species co-occurred significantly more than expected by chance. The canonical correlation analyses for the Vargem Grande and Pau da Fome areas area showed a significant relationship between black fly abundances and predator abundances. In Vargem Grande the abundance of Chironomidae showed a highly significant positive correlation to S. (Psaroniocompsa) sp., while Hydropsychidae was significantly correlated to Simulium sp. On the other hand, in Pau da Fome Libellulidae was significantly correlated to S. (Psaroniocompsa) sp. and Simulium sp. and Chironomidae correlated significantly to Simulium sp. The result is consistent with what would be expected of organisms that exercise mutual population regulation, although other factors than biotic interactions may be causing these patterns. However the lack of mechanistic evidences on the effect of biotic interactions on black fly populations pose a challenge on the understanding of these patterns.